Concurrent asynchronous robotic subsumption using actors & promises - Ratnesh Srivastav; G. C. Nandi; Rohit Shukla; Harsh Verma (Institute of Advanced Engineering and Science, 2019)
Fascinated with robotics open source integrated component MARIE [1], ROS [5] and open source component PLAYER/STAGE [2], CARMEN [3] available in the eld of robotics application. We aim at developing an asynchronous concurrent robotics application based on subsumption [6] architecture using PLAYER, STAGE and already available services freely available on the internet. We used wanderer and wall follower services embedded inside an actor [10][11] and integrated these services to two dierent robots of same congurations on our promise based frame-work that provides actor as service. The two robots switch their services based on color detected (red,green,blue) during their movement in an environment asynchronously. Using actor as a service lls the gap of SOA [4] & EDA [7] by providingsynchronous and asynchronous support for communication. We measured the performance of time taken in completion of services in promise [8] based implementation ,synchronous and asynchronous callback [9] based implementation. We developed a model to prove deadlock freeness in our integrated architecture using petrinet [15] interface composition. We have also been able to justify that component integrated on promise based framework takes less time in service completion than synchronous and asynchronous callback based services.